English as a Treat and a Threat: Why teachers should be Aware of Critical Language Awareness - Delvi Wahyuni (Universitas Negeri Padang, 2014)
Charlemagne, King of the Franks once remarked that to have another language is like to have a second soul. This remark strongly emphasizes that having a command of several languages is beneficial. For this reason, aside from the learning of the national language, foreign languages are also included in school curriculum in Indonesia. Among all of foreign languages taught at schools, it is English which attains privileged position due to its states as one of the subjects which students must pass in the national examination system known as UN along with Math, Science and Bahasa Indonesia. Its privileged position also transpires to other fields such as the job market, academic achievement, and career development. As a result, there is a growing demand for the mastery of English for it has been associated with success and higher social stand. However, aside from the benefits it boasts, this frenzy over English proficiency has a potential to be damaging to the national language and culture. It is the objective of this paper to explain the treat the English language has to offer, and the threat in store for an uncritical learning of this language. Thus, in order to maximize our exploit of English for our national interest and to ward off the danger it poses, I propose critical language awareness as an approach in our pedagogic practice.